2015
DOI: 10.1080/13607863.2015.1099034
|View full text |Cite
|
Sign up to set email alerts
|

Fear of falling and its predictors among community-living older adults in Korea

Abstract: A multidimensional construct of general characteristics, physical, and psychosocial variables act as risk factors for FOF. Preventive intervention should be developed to decrease the FOF among Korean older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 44 publications
9
50
1
2
Order By: Relevance
“…12 In accordance with this study, we hypothesize that FOF is associated with lower satisfaction with life. 12 In accordance with this study, we hypothesize that FOF is associated with lower satisfaction with life.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…12 In accordance with this study, we hypothesize that FOF is associated with lower satisfaction with life. 12 In accordance with this study, we hypothesize that FOF is associated with lower satisfaction with life.…”
Section: Introductionsupporting
confidence: 80%
“…A recent cross-sectional study among communitydwelling older adults in Korea showed that FOF is associated with decreased life satisfaction. 12 In accordance with this study, we hypothesize that FOF is associated with lower satisfaction with life. This might be explained by the positive link between life satisfaction and extraversion in individuals.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, its prevalence among the elderly population is substantially high. Many studies have reported that an average of 21-85% of the elderly population has FOF [5][6][7][8]. The various risk factors that have been identified to be associated with FOF are previous history of falling, impaired gait, imbalance, unsteadiness, muscle weakness and limitation of daily tasks [9,10].…”
Section: Introductionmentioning
confidence: 99%